The Effort of The Government and Its Impact on Maintaining the Stability of Cooking Oil Prices - Mohamad Nur Efendi; Shidqi Saifuddin Hamzah; Selvina Khomairoh; Nurul Izzati Septiana (Fenomena, 2024)
The surge in global oil prices and the consequent scarcity of oil have significantly impacted cooking oil prices in Indonesia, making it a critical issue for analysis. Previous studies have often overlooked governmental interventions' immediate and long-term effects on cooking oil prices, leaving a gap in understanding their comprehensive impact on traditional market economies. This article evaluates the Indonesian government's policy responses, including oil subsidies and export bans, to mitigate cooking oil price hikes and their effects on traditional markets. Field research was conducted at the Srijaya Sayur Traditional Market in Madiun City using qualitative methods. While the study provides valuable insights, it is important to acknowledge its limitations, such as the focus on a single market and the potential bias in the data gathered through interviews. The analysis revealed that the government's abrupt intervention caused market distortions, such as distribution issues and price inconsistencies. However, these issues diminished over time as oil stock levels increased and enforcement actions against illegal activities were strengthened. This study contributes new insights into the effectiveness of policy interventions and highlights the alignment with Ibn Taymiyah's principles of distribution justice. In conclusion, while the policies initially disrupted market stability, they ultimately stabilized prices and aligned with consumer purchasing power.